The Andy Cohen diaries [compact disc, unabridged] : a deep look at a shallow year - Cohen, Andy, 1968- (Macmillan Audio, 2014)
Andy Cohen has a front row seat to an exciting world not many get to see. In this dishy, detailed diary of one year in his life, Andy goes out on the town, drops names, hosts a ton of shows, becomes codependent with Real Housewives, makes trouble, calls his mom, drops some more names, and, while searching for love, finds it with a dog.